AIDS-related malignancies. Issue 1 (January 2016) - Qadir, Muhammad I.; Abbas, Khizar; Qadeer, Kahkashan; Abid, Amman
Abstract : There is a high risk of developing malignancies in persons infected with HIV. The most common AIDS-related cancer is Kaposi's sarcoma, which is caused by Kaposi's sarcoma-linked herpesvirus. Others are invasive cervical cancer and non-Hodgkin's lymphoma caused by human papillomavirus and Epstein–Barr virus, respectively. Among the chemotherapeutic agents, pegylated liposomal doxorubicin is an effective therapy for patients with HIV-linked Kaposi's sarcoma. There is also a chance of developing non-AIDS-related cancers, for example, Hodgkin's disease and multiple myeloma. Use of highly active antiretroviral therapy is very important for controlling the malignancies, as well as the occurrence of long-term infections and prognosis.